2000
DOI: 10.1103/physrevb.61.4259
|View full text |Cite
|
Sign up to set email alerts
|

Entropy, vortex interactions, and the phase diagram of heavy-ion-irradiatedBi2Sr2CaCu

Abstract: Dynamic and thermodynamic magnetization experiments on heavy-ion irradiated single crystalline Bi2Sr2CaCu2O 8+δ are correlated in order to clarify the nature of the mixed state phase diagram. It is shown that whereas the entropy contribution to the free energy in the London regime plays a minor role in unirradiated crystals and irradiated crystals at fields close to or above the matching field B φ , it becomes very important at low fields in irradiated crystals with high B φ . The direct determination of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…In order to demonstrate that columnar defects were effectively produced in these samples, we measured the reversible magnetization and found that it exhibited the same behavior as for the optimally doped crystals irradiated at room temperature. 3 However, the local ac transmittivity of UN75-LT-n showed an increase of T c when it was measured half a year after the LT irradiation, having been kept at room temperature in nitrogen for 90 days and in air for another 90 days. As shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to demonstrate that columnar defects were effectively produced in these samples, we measured the reversible magnetization and found that it exhibited the same behavior as for the optimally doped crystals irradiated at room temperature. 3 However, the local ac transmittivity of UN75-LT-n showed an increase of T c when it was measured half a year after the LT irradiation, having been kept at room temperature in nitrogen for 90 days and in air for another 90 days. As shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Most investigations have been concerned with the exploration of vortex pinning, flux flow, and novel vortex matter phase transitions due to the introduction of CD's. [1][2][3][4][5] It has often been reported that the heavy-ion irradiation caused a modification of T c , but this effect, as well as the effect of heavy-ion irradiation on other superconducting parameters and material properties, has not been studied in great detail. Only recently evidence was obtained that an important part of the T c change of high-T c Bi 2 Sr 2 Ca n1 Cu n O 2nϩ4ϩx (n ϭ1, 2͒ thin films after heavy-ion irradiation is due to the motion of oxygen and self-doping of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…This field-evolution of the irreversibility line is common to Bi 2 Sr 2 CaCu 2 O 8 samples with high-densities of CD and has origin in the three different regimes for the occupation of columnar defects with vortices discussed in Refs. 38,39. Figure 1 also indicate with dotted lines the H -T paths followed during the field-cooling magnetic decoration experiments.…”
Section: A Vortex Phase Diagrammentioning
confidence: 94%
“…To better understand the underlying physics, we use the vortex-defect interaction model of Wahl et al [16,17]. Their analysis provides that…”
Section: Resultsmentioning
confidence: 99%